2016
DOI: 10.1007/s00296-016-3626-9
|View full text |Cite
|
Sign up to set email alerts
|

A case of urticarial vasculitis in a female patient with lupus: Mycoplasma pneumoniae infection or lupus reactivation?

Abstract: A 17-year-old female patient affected by systemic lupus erythematosus (SLE) (who had been taking 300 mg/die of hydroxychloroquine for 3 years), Graves' disease (treated with 10 mg/die of tapazole), and celiac disease came to our attention for urticarial vasculitis. She had been taking prednisone (25 mg/die) for 3 days, and her blood tests showed high levels of Mycoplasma pneumoniae IgM and IgG antibodies. The association between urticaria and M. pneumoniae infections can be present in up to 7% of the cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…However, the IgG level showed an increasing trend after 2 weeks, indicating temporal changes in IgA, IgM, and IgG levels differ after MP infection. In several studies, the serum IgA, IgM, and IgG levels of critically ill children were significantly higher than in mildly ill children, indicating the humoral immunity becomes increasingly compromised with the progression of MP infection 2 . In several studies, the serum total IgE levels were higher in the atopic patients than in the nonatopic patients with increased IgE levels 22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the IgG level showed an increasing trend after 2 weeks, indicating temporal changes in IgA, IgM, and IgG levels differ after MP infection. In several studies, the serum IgA, IgM, and IgG levels of critically ill children were significantly higher than in mildly ill children, indicating the humoral immunity becomes increasingly compromised with the progression of MP infection 2 . In several studies, the serum total IgE levels were higher in the atopic patients than in the nonatopic patients with increased IgE levels 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma pneumoniae (MP) is a common pathogen of community‐acquired pneumonia in children 1 . When MP infection occurs in infants and young children, it causes inflammation of respiratory tracts and immune system disorders 2 such as arthritis, myocarditis, and thrombosis. Multiple organ failure might occur in severe cases 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As in other autoimmune conditions, both innate and adaptive immunity play a role in disease pathogenesis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vasculitis etiologic factors are diverse and include infectious agents (15-20%), inflammatory conditions (15-20%), medications (10-15%) and neoplasms (5%), with 45-55% of cases not having an etiologic diagnosis 5,[18][19][20] .In tertiary care referral centers, SLE-associated vasculitides occur more often in adult patients 21 . Vasculitis clinical diagnosis must be confirmed by anatomopathological study, where loss of vascular architecture is observed, caused by wall infiltration by neutrophils, lymphocytes or histiocytes; the presence of fibrinoid necrosis is characteristic 22 .…”
Section: Introductionmentioning
confidence: 99%